For-Profit Universities in the Political Economy of Higher Education - Pusser, Brian (International Higher Education, 2008)
For-profit institutions loom much larger in the political economy of US higher education. In negotiations over the reauthorization of the Higher Education Act, the for-profit universities and their lobbying organizations have played a unique role in shaping policies affecting all higher education institutions. Can states preserve egulations that protect the public and private benefits of higher education while satisfying the profit demands of an evolving postsecondary market? As with most political contests, much will depend on the ability of a variety of postsecondary stakeholders to become involved in the political arena shaping higher education.